Routledge Handbook of the Digital Environmental Humanities (Taylor & Francis, 2023)
Cartography, Computing, Digital environmental humanities, Digital methods, Digital tools, Environment and sustainability, Environmental humanities, Environmental literature, Human geography, Indigenous, Informatics, Nature, Virtual spaces
English
Keywords: Applied ecology; Graphical and digital media applications; Language: reference and general; Cartography, Computing, Digital environmental humanities, Digital methods, Digital tools, Environment and sustainability, Environmental humanities, Environmental literature, Human geography, Indigenous, Informatics, Nature, Virtual spaces